Estudo de ferramentas estatísticas para a análise de itens em relatórios pedagógicos - Baptista, Isabela Maria Melle (Universidade Federal de São Carlos, 2022)
This degree final monograph the analysis of math items in pedagogical reports of external evaluations. In this direction, it is pointed out in the literature that math teachers have difficulties in interpreting and in making such reports. Aiming to fill this gap and in a qualitative-quantitative perspective, this work approaches, from a theoretical point of view, the main tools of educational assessment and the Classical Test Theory (TCT) present in official government reports. From a practical point of view, this work interpreted the 2017 SAEB Report with regard to the analysis of math items. In order to facilitate the calculation of statistical coefficients by teachers/managers, dynamic electronic spreadsheets that calculate certain TCT indices were implemented. Last, a case study is carried out with ENEM Mathematics items from the 2019 edition, in which, from a random sample of responses, the worksheet was applied and some items analyzed.
A study of statistical tools for item analysis in pedagogical reports
Keywords: Avaliação educacional; Teoria clássica de testes; Relatórios do SAEB; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS